The Impact of Workforce Capability Development and Competitive Compensation Incentives on Workplace Commitment Mediated by Work Engagement at CV. Ayo Usaha - Yunita Qomariyah; Jati Waskito (Program Pascasarjana STIE Amkop Makassar, 2026)
This research investigates the influence of workforce capability enhancement and competitive remuneration incentives on employee commitment, with work engagement functioning as a mediating variable within the staff of CV. Ayo Usaha. A quantitative research methodology utilizing a causal design was adopted. Primary data were gathered via a questionnaire survey targeting 120 permanent employees and were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results reveal that workforce capability enhancement and competitive remuneration incentives significantly and positively impact work engagement and employee commitment. Additionally, work engagement serves as a significant mediator in the relationship between both independent variables and workplace commitment. These findings underscore the critical role of employee capability enhancement and equitable compensation structures in promoting work engagement and reinforcing organizational commitment.